Study on the variable pitch control of the wind power unit based on mamdani inference and conventional control algorithm. Issue 1 (July 2020) - Rashid, Asif; Ying, Deng
Abstract: This paper firstly analysed the theory of the Wind Turbine (WT) pitch control algorithms to maximize energy yield, and then based on the analysis, 3 MW wind turbine model with a servo system and Doubly Fed Induction Generator (DFIG) is developed. The blade pitch ß angle is controlled to ensure that the variable speed WT system operate safely and the optimum power is achieved. Variation in rotor speed as a result of unsteady wind velocity is controlled using PI(D) method. Fuzzy technique is developed and implemented simultaneously. Control Algorithms reveal dynamic performance of the blade pitch angle, rotor speed and rated power characteristics. Within the wind turbine standard operating regimes, controllers have shown promising results. Proposed Fuzzy technique validates superior performance. Finally, MATLAB/SIMULINK tool box establishes the corresponding model to simulation test in order to verify the effectiveness and correctness of the analysed algorithms. Simulation result demonstrates that the developed pitch servo control system has good dynamic, steady state performance and robustness.